Sirtuin Modulators in Cellular and Animal Models of Human Diseases - Hong, Jun Young; Lin, Hening (Frontiers in Pharmacology, 2021)
Sirtuins use NAD+ to remove various acyl groups from protein lysine residues. Through working on different substrate proteins, they display many biological functions, including regulation of cell proliferation, genome stability, metabolism, and cell migration. There are seven sirtuins in humans, SIRT1-7, each with unique enzymatic activities, regulatory mechanisms, subcellular localizations, and substrate scopes. They have been indicated in many human diseases, including cancer, neurodegeneration, microbial infection, metabolic and autoimmune diseases. Consequently, interests in the development of sirtuin modulators have increased in the past decade. In this brief review, we specifically summarize genetic and pharmacological modulations of sirtuins in cancer, neurological, cardiovascular diseases. We further anticipate this review will be helpful for scrutinizing the significance of sirtuins in the studied diseases.